Colchicine attenuates chemical hypoxia-induced pyroptosis through downregulation of nuclear factor kappa B and caspase-1 in cardiomyocytes - Satrijo, Budi; Rohman, Mohammad S.; Aulanni'am, Aulanni'am; Sujuti, Hidayat; Lestari, Bayu (Narra Sains Indonesia, 2025)
Myocardial infarction (MI) is the leading cause of mortality worldwide. During MI, cardiomyocyte necrosis and inflammation are crucial in the post-MI cardiac remodeling process, including pyroptosis. Although colchicine is a well-known anti-inflammatory drug that has been clinically studied in the context of MI, its role in cardiac pyroptosis remains unclear. The aim of this study was to investigate the role of colchicine in pyroptosis in vitro, using CoCl2-induced H9c2 cells. Prior to the primary experiment, the hypoxic model in H9c2 cells was optimized by evaluating hypoxia-inducible factor-1 alpha (HIF-1α) expression and viability in cells exposed to various concentrations of CoCl2 at different time intervals. Subsequently, an in vitro hypoxia model was established by treating H9c2 cells with CoCl2 (600 µM), with or without colchicine (1 µM), for 3 hours. Flow cytometry was used to measure the expression of nuclear factor-kappa beta (NF-κB), interleukin 18 (IL-18), caspase-1, and HIF-1α in pyroptotic cells. Immunofluorescence was used to assess caspase-1 localization and its colocalization with propidium iodide during late-stage pyroptosis. Our data indicated that CoCl2-induced hypoxia significantly upregulated NF-κB, caspase-1, and IL-18 expression, and increased pyroptotic cell death in H9c2 cells. Colchicine treatment attenuated these effects, leading to a marked reduction in NF-κB, caspase-1, and IL-18 expression in hypoxic cells. Colchicine treatment significantly decreased the number of late pyroptotic cells. The protective effect of colchicine was more pronounced in late hypoxia (24-hour) setting compared to early hypoxia (3-hour). These findings suggest that colchicine attenuates cardiac pyroptosis in hypoxic H9c2 cells, as evidenced by the significant downregulation of key proteins involved in this pathway, including NF-κB, caspase-1, and IL-18. This protective effect appeared to be more effective in late hypoxia.